FELINE PANLEUKOPENIA VIRUS INFECTION: A COMPREHENSIVE REVIEW (2010–2025) - H.J. Apoorva; V.S. Lathamani; P.T. Ramesh; Shivaraj B. Murag; R. Sudharani; M.P. Veena (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Feline  panleukopenia  (FPL)  is  a  highly  contagious  viral  disease  caused by feline panleukopenia virus (FPV), affecting cats across all age groups. FPV is classified under Carnivore Protoparvovirus 1, within the genus Protoparvovirus of the Parvoviridae  family,  which  includes  three  subfamilies:  Parvovirinae,  Densovirinae and  Hamaparvovirinae.  Clinical  severity  varies  with  age,  immune  competence and the presence of secondary infections. Typical signs include lethargy, anorexia, fever,  vomiting,  diarrhea,  and  leukopenia.  Diagnosis  is  based  on  clinical  signs and  hematological  findings,  confirmed through  polymerase  chain  reaction  (PCR) or rapid antigen detection kits. Recent diagnostic advances, such as nano-PCR and isothermal amplification techniques, have enhanced detection speed and sensitivity. Treatment is supportive, as no specific antiviral exists. Core interventions include intravenous fluids, electrolyte correction, antiemetics, and broad-spectrum antibiotics to manage secondary bacterial infections. Nutritional support is vital for recovery. In severe cases, blood transfusions or immunomodulators such as interferon-omega or granulocyte colony-stimulating factor (G-CSF) may be indicated. Early intervention and  strict  biosecurity  are  critical  for  successful  outcomes  and  disease  control.